Festival Publicatessen: a tool for the integration of academic and professional skills - Martín García, Noemí; Martín García, Alberto; Núñez Cansado, María Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The Publicatessen Festival has been held for fourteen editions on the María Zambrano campus of the University of Valladolid. It is organized by students in the fourth year of the degree in Advertising and Public Relations, with the direct coordination of the teaching staff. The objective of this publication is to know the assessment of those former students who have achieved, and to know what skills they have developed for their professional life. The results show that it is a very positive action for them and they recognize it as fundamental for their training in the world of Advertising.